2014
DOI: 10.1103/physrevb.89.220406
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Hall effect in epitaxialL10-Mn1.5Ga films with variable chemical ordering

Abstract: Abstract: The transport behaviors of weak localization and anomalous Hall effect (AHE) in perpendicularly magnetized L1 0 -Mn 1.5 Ga single-crystalline films are investigated as a function of degree of long-range chemical ordering and temperature. We observed significant weak localization and metal-insulator transition in highly disordered films. Our results provide new evidence that weak localization, phonons and magnons have negligibly smaller effect on extrinsic AHE resistivity than static defects for all t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Therefore, it is of extreme importance to control the low- T transport behaviors for a better SV performance, for instance, via taking advantage of the structural disorder effects of Co 2 MnAl films. Structural disorder such as impurities, strain, and dislocations in Mn-based alloys has been proved to account for the large variations in magnetooptical Kerr effects1516, Gilbert damping17, magnetic anisotropy18, anomalous Hall effect19, and for the occurrence of electronic disorder physics (e.g. weak localization20 and atomic tunneling effects212223).…”
mentioning
confidence: 99%
“…Therefore, it is of extreme importance to control the low- T transport behaviors for a better SV performance, for instance, via taking advantage of the structural disorder effects of Co 2 MnAl films. Structural disorder such as impurities, strain, and dislocations in Mn-based alloys has been proved to account for the large variations in magnetooptical Kerr effects1516, Gilbert damping17, magnetic anisotropy18, anomalous Hall effect19, and for the occurrence of electronic disorder physics (e.g. weak localization20 and atomic tunneling effects212223).…”
mentioning
confidence: 99%
“…In common magnetic metals, e.g. Fe and L10-Mn1.5Ga [7,10], ρAH are always observed to decrease monotonically as T decreases. In striking contrast, ρAH of our L10-MnAl films shows non-monotonic T dependence.…”
mentioning
confidence: 99%
“…Notably, in contrast to the conventional picture that ρAH scales with the total resistivity irrespective of its sources [3], recent experimental studies have revealed that both ρAH and the scaling relation are qualitatively different for various types of electron scattering. Phonon scattering was found to have no distinguishable contribution to extrinsic part of ρAH in ferromagnetic Fe, Co, Ni, L10-Mn1.5Ga films, Co/Pt multilayers, and paramagnetic Ni34Cu66 films [7][8][9][10][11][12]. When ρxx is dominated by phonon and static defect scattering, the AHE has a scaling of ρAH = a0 ρxx0+bρxx 2 , where ρxx0 is the residual resistivity, a0ρxx0 is the extrinsic contribution from both side jump and skew scattering, and b is the intrinsic anomalous Hall conductivity (AHC).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Fe(001) thin films [20], the parameter b referring to intrinsic contribution was proved to be thickness independent, which agreed with the intrinsic values measured in Fe whiskers [26] and calculated for Fe(001) perfect crystal [27]. The validity of this scaling was fully tested in thin films of Fe [20,21], Co [23], Ni [28], amorphous CoFeB [29], and chemical-ordered MnGa [30] and was justified by theoretical work [24]. At low temperatures, the resistivity q xx and the anomalous Hall resistivity q ah change slowly with temperature and thus approximately equal to q xx0 and q ah0 .…”
Section: Data Analysis and Discussionmentioning
confidence: 62%